2012
DOI: 10.1149/2.068212jes
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a Silicotungstic Acid Functionalized Carbon on Pt Activity and Durability for the Oxygen Reduction Reaction

Abstract: Colloidal Pt prepared by an ethylene glycol reduction method was deposited onto Ketjen black carbon supports functionalized with (0, 3.2, 7.1, and 15.9wt%) 11-silicotungstic acid (Pt/SiW 11 -C). Electrochemical characterization of the catalysts was performed using rotating disk electrodes (RDE) in 0.1 M HClO 4 electrolyte. XRD and TEM showed smaller crystallite size and more uniform deposition of Pt nanoparticles for Pt/SiW 11 -C catalysts, respectively. A maximum in the ORR mass activity of 373 mA/mg Pt was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Wlodarczyk et al concluded that for the operating conditions for oxygen reduction all heteropolyacids should remain stable on platinum and carbon. 27 durability on carbon following 6000 cycles between 1.0 and 1.6 V. 40 Degradation testing is used to simulate life-time testing and evaluate the PEMFC components and performance parameters over a short period of time. During extended cell testing at 120 • C/35% RH and during degradation testing electronic shorts were observed in some cells as seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wlodarczyk et al concluded that for the operating conditions for oxygen reduction all heteropolyacids should remain stable on platinum and carbon. 27 durability on carbon following 6000 cycles between 1.0 and 1.6 V. 40 Degradation testing is used to simulate life-time testing and evaluate the PEMFC components and performance parameters over a short period of time. During extended cell testing at 120 • C/35% RH and during degradation testing electronic shorts were observed in some cells as seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mason et al showed an increase in ECSA on functionalized carbon with SiWA loadings up to 7.1% and then a decrease at higher loadings. 40 Polarization curves were obtained for cells containing 3, 6, 15% SiWA using the blend fabrication, 16% SiWA for the soak fabrication, 15% SiWA using the pH modified fabrication and 0.5 and 2.5 M SiWA dip fabrication to evaluate performance against the established baseline. Data were collected at 80 • C/100% RH on H 2 /air and H 2 /O 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, according to the literature, hybrid polymer-silicotungstic acid (STA) membranes have a high thermal stability, promising mechanical strength and proton conductivity [10,[15][16][17][18]. Moreover, the addition of STA to the electrodes of polymer electrolyte membranes fuel cells is reported to enhance the activity of platinum towards oxygen reduction reaction and the stability of the membrane [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…19,20 A method of covalent bonding HPAs to carbon in the catalyst layer has also shown some improvements in chemical stability, but chemical degradation mitigation within the membrane is needed. 21,22 Our group has developed two membrane platforms with HPAs covalently attached and immobilized within a polymer membrane, serving as the proton conducting acid. [23][24][25][26] More recently, the outstanding chemical stability of one of these platforms has been demonstrated, 26 however, the stability demonstrated in this study was criticized for using rather thick, 80 μm membranes in subscale fuel cells.…”
mentioning
confidence: 99%